Prevalence and determinants of fasted training in endurance athletes: a survey analysis - Rothschild, J. A.; Kilding, A. E.; Plews, D. J. (International Journal of Sport Nutrition and Exercise Metabolism, 2020)
Athletes may choose to perform exercise in the overnight-fasted state for a variety of reasons related to convenience, gut comfort, or augmenting the training response, but it is unclear how many endurance athletes use this strategy. We investigated the prevalence and determinants of exercise performed in the overnight-fasted state among endurance athletes using an online survey and examined differences based on sex, competitive level, and habitual dietary pattern. The survey was completed by 1,950 endurance athletes (51.0% female, mean age 40.9 ± 11.1 years). The use of fasted training was reported by 62.9% of athletes, with significant effects of sex (p < .001, Cramer`s V [fc] = 0.18, 90% CI [0.14, 0.22]), competitive level (p < .001, fc = 0.09, 90% CI [0.5, 0.13]), and habitual dietary pattern noted (p < .001, fc = 0.26, 90% CI [0.22, 0.29]). Males, nonprofessional athletes, and athletes following a low-carbohydrate, high-fat diet were most likely to perform fasted training. The most common reasons for doing so were related to utilizing fat as a fuel source (42.9%), gut comfort (35.5%), and time constraints/convenience (31.4%), whereas the most common reasons athletes avoided fasted training were that it does not help their training (47.0%), performance was worse during fasted training (34.7%), or greater hunger (34.6%). Overall, some athletes perform fasted training because they think it helps their training, whereas others avoid it because they think it is detrimental to their training goals, highlighting a need for future research. These findings offer insights into the beliefs and practices related to fasted-state endurance training.